Pendekatan Melalui Evolusi Konteks Relasi Media Sebagai Lensa Media Sosial Dalam 'Business Budgeting on the Method Perspective' - Hefri Yodiansyah; Debby Kurniadi (Jurnal Ilmu Sosial dan Humaniora, 2022)
The social context in social media is determined by 'Business Budgeting on the Method Perspective' study of identifying problems at the level of social information services, through cost budgeting efforts in the context of rising inflation and elements of geopolitical instability manifested by buying and selling recession and social insecurity, especially for low-income residents. The purpose of this finding is to identify the problems of the current situation affecting the social status of citizens and the prospects for exploiting the costs of their evolution by introducing a quality index of social needs based on statistical and econometric forecasting methods. The alternative perspective method used is empirical, represented by special literature studies, data analytics, database consolidation, econometric modelling, prospective analysis, and economic forecasting. This social conceptualization in making rational discussions is determined by the degree of social security issues, prevention efforts in the context of creating inflation and elements of geo-political instability manifested by recession and social vulnerability, especially for residents with micro-regions. This study aims to identify the actual situation affecting the social status and the perspective of its evolution as an asset by introducing a social security index based on statistical and econometric prediction methods. This method uses natural experiences that represent specific literature studies and natural analysis, each of which 'business budgeting on the method perspective' consolidates the field of scholarly dates, field models of econometrics, prospective analysis and previous economics.